Measuring the Digital Marketing Strategies Effectiveness through Social Media in Purchasing Halal Make Up Brands: A Comparative Study (Penelitian Perbandingan: Keefektifan Iklan, Celebrity Endorsement, dan Influencer Marketing dalam Memengaruhi Niat Beli Merk Make-up Halal) - nfn Yulianita; Nadira Ulva; Rand Rasyid (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2020)
Nowadays, marketers utilize online channels to reach for the target market. There are plenty of tactics that can be used, such as advertisement, celebrity endorsement, and influencer marketing. This research aimed to compare the effectiveness of each tactic to influence purchase intention towards halal make-up brand. Wardah is the research subject. The researcher used the mixed method sequential exploratory that consisted of two phases. The first phase was qualitative and the second phase was quantitative. During the first phase, the researcher interviewed 25 informants to explore indicators for proposed variables. Based on the first phase finding, the instrument for the second phase was developed. During the second phase, the researcher collected data from 154 respondents. The findings indicated that the advertisement, celebrity endorsement, and influencer marketing simultaneously and partially had significant influence on purchase intention. Comparing all three tactics, influencer marketing had the most significant influence on purchase intention.